2018
DOI: 10.1088/1742-6596/997/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, thickness and sheet resistivity of Cu/Ni thin film produced by electroplating technique on the variation of electrolyte temperature

Abstract: Abstract. In this research, it has been made Cu/Ni thin film produced with electroplating technique. The deposition process was done in the plating bath using Cu and Ni as cathode and anode respectively. The electrolyte solution was made from the mixture of HBrO3 (7.5g), NiSO4 (100g), NiCl2 (15g), and aquadest (250 ml). Electrolyte temperature was varied from 40C up to 80C, to make the Ni ions in the solution easy to move to Cu cathode. The deposition was done during 2 minutes on the potential of 1.5 volt. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Sensor performance data will be displayed on the logger pro software. Determining the sensitivity of the sensor is by looking at the relationship between the RTD voltage value and the temperature change which is then processed with second-order polynominal data fitting [25], as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Sensor performance data will be displayed on the logger pro software. Determining the sensitivity of the sensor is by looking at the relationship between the RTD voltage value and the temperature change which is then processed with second-order polynominal data fitting [25], as follows:…”
Section: Methodsmentioning
confidence: 99%
“…For the nozzle with a depth of 100 µm, the electrode's feed depth should be 90 µm when the thickness of the coating at the outlet is controlled. Due to the effects of current efficiency and the area ratio of the cathode to anode in actual machining [33,34], the potential difference is set to 0.1 V between the electrode and the work piece. As shown in figure 7, the current density distribution of the inner surface is simulation analyzed with the electrode's feed depth at 90 µm.…”
Section: Electroplating Process Simulation and Designmentioning
confidence: 99%
“…The DC, PC, and PRC electrodeposition techniques have been employed to develop various alloy coatings, such as Ni-Fe, 28 Ni-P, 29 Ni-W, 30 Ni-Cr, 31 and Cu-Ni. 32 In our previous work, 11,12 we have shown that DC electrodeposited G-reinforced CuNi nanocomposite coatings exhibit remarkable mechanical, wear, and anti-corrosion properties compared with CuNi coatings. A scientific report on the electrodeposition of CuNi-G nanocomposite coatings through PC and PRC techniques is not available in the literature to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 95%